Environmental regulation tools and corporate environmental information disclosure: Evidence from a-share-listed companies in Shenzhen and Shanghai, China - Luo, Xiaobin; Jaidi, Junainah; Nipo, Debbra Toria (Asian Development Policy Review, 2023)
Environmental accounting is not only a more comprehensive and effective accounting model but also a more beneficial monitoring model for ecological protection and social development. Environmental accounting enables companies to develop economic benefits while protecting and managing the environment and to assume corresponding social responsibilities and obligations. Based on the importance of environmental regulation, this study attempts to evaluate the role of environmental regulatory tools in corporate environmental information disclosure using the Environmental Information Disclosure Index (EIDI) as a proxy variable. The regression analysis conducted on a panel dataset encompassing all A-share listed companies in the Shanghai and Shenzhen stock markets from 2007 to 2018 reveals a significant relationship between environmental regulatory tools and EIDI. Specifically, the Control command type, Public Participation Type, and Voluntary action-oriented Type have a positive and significant influence on corporate environmental information disclosure, whereas the Market Incentive Type has a negative and significant influence. This evidence suggests that the reasonable use of environmental regulatory tools is an important means of improving the quality of corporate environmental information disclosure.